Community Empowerment Model Based on Independence in Administration Alert Village Health Sector - Suparji, Suparji; Nugroho, Heru Santoso Wahito; Sunarto, Sunarto (Health Notions, 2018)
Introduction: The success of âAlert villagesâ (âalert villageâ) can be explained using an independence-based "community empowerment model", involving factors of physical capital, human capital, social capital and community empoweredness. Method: This model was developed with a cros sectional design involving physical capital, human capital, social capital, community empoweredness, and âalert villageâ success. The research subjects were 216 implementers of âalert villageâ in Panekan Sub-district, Magetan District, selected by cluster sampling technique. Data were collected through questionnaires, then analyzed using structural equation modeling based on partial least square. Result: The success of âalert villageâ wass influenced by: 1) physical capital with total effect of 0.105360; 2) social capital with total effect 0.774022, 3) community empoweredness with total effect 0.952891. Analysis: The success of âalert villageâ was determined by a direct determinant of community empoweredness and two indirect determinants of physical capital and social capital. Discussion: In the model of community empowerment in the implementation of âalert villageâ in Panekan Sub-district, the success of âalert villageâ was determined by 2 main factors in sequence, namely: 1) community empoweredness that included the ability to identify and develop potential, identify and prioritize problems, solve the problem; 2) social capital that included social network, level of trust between people, obedience to norm, caring for others, and involvement in implementation.